Narrative in the professional age : transatlantic readings of Harriet Beecher Stowe, George Eliot, and Elizabeth Stuart Phelps - Cognard-Black, Jennifer, 1969- (Literary criticism and cultural theory., 2004)
Challenging previous studies that claim anxiety and antagonism between transatlantic Victorian authors, Jennifer Cognard-Black uncovers a model of reciprocal influence among three of the most popular women writers of the era.